Posouzení informačního systému firmy a návrh změn - Plojhar, Jan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Diplomová práce se zaměřuje na posouzení a zhodnocení informačního systému podniku Plojhar s.r.o. a na návrh změn pro jeho zlepšení. Teoretická část obsahuje vymezení základních pojmů, týkajících se tématu informačních systémů a přístupů k jejich hodnocení, řízení a správě. V další, analytické části, je informační systém zkoumán z několika pohledů a je provedena jeho komplexní analýza. Na základě analýzy jsou následně navržena možná řešení změn informačního systému.

The Master’s Thesis focuses on examination and assessment of information system in the Plojhar s.r.o. company and on proposal of changes for its improvement. The theoretical part contains definitions of the basic concepts relevant to the subject of information systems and approaches to their assessment, management and administration. In the next, analytical part, the information system is examined from several points of view and a complex analysis is performed. Possible solutions of changes of the information system are presented on the basis of the analysis.
Information System Assessment and Proposal for ICT Modification
Keywords: Informační systém; informace; data; informační technologie; informační strategie; výrobní podnik; metoda HOS 8; informační bezpečnost; Information system; information; data; information technology; information strategy; production company; HOS 8 method; information security